The Effect of Learning Discipline on Independence Student Learning - Yuyun Elizabeth Patras; Nur Baeti Sabti; Tustiyana Windiyani; Rais Hidayat (Pedagonal : Jurnal Ilmiah Pendidikan, 2021)
The Influence of Learning Discipline on Students Independent Learning. Primary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Bogor 2020. This research is a quantitative study with a causal approach. This study aims to determine the effect of learning discipline on the learning independence of fifth grade students at Gunung Gede State Elementary School, North Bogor District, Bogor City. The population of this study was 117 students with a total sample of 54 students. This research was conducted in the even semester of the 2019/2020 school year. The results of the study show that the influence of learning discipline on student learning independence is shown by statistical analysis that shows produce a correlation coefficient (rxy) of 0.38. This shows that there is an influence between learning discipline on student learning independence, while the coefficient of determination (r2) of 0.14 or 14%. The remaining 86% is determined by another factor. The average student learning independence of 14% is determined by the discipline of learning through the regression equation = 54.93+(0.41X), meaning that each unit increase in the value of learning discipline will cause an increase in student learning independence by 0.41 units. Based on the results of this study, it can be concluded that there is a positive influence between learning discipline on student learning independence in fifth grade students of Gunung Gede State Elementary School, North Bogor District, Bogor City, Even Semester of the 2019/2020 Academic Year.